1995
DOI: 10.1155/1996/94696
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Low Power Ternary Full Adder

Abstract: In this work, the design and implementation of a low power ternary full adder are presented in CMOS technology. In a ternary full adder design, the basic building blocks, the positive ternary inverter (PTI) and negative ternary inverter (NTI) are developed using a CMOS inverter and pass transistors. In designs of PTI and NTI, W/L ratios of transistors have been varied for their optimum performance. The ternary full adder and its building blocks have been simulated with SPICE 2G.6 using the MOSIS model paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Srivastava et al has shown that balanced ternary full adders can be designed with CMOS using a dual power supply [29]. Balla et al also presented the design of a MOS ternary logic family [30].…”
Section: Microelectronics For Ternary Computersmentioning
confidence: 99%
“…Srivastava et al has shown that balanced ternary full adders can be designed with CMOS using a dual power supply [29]. Balla et al also presented the design of a MOS ternary logic family [30].…”
Section: Microelectronics For Ternary Computersmentioning
confidence: 99%
“…It is worth mentioning that the proposed method of designing ternary structures significantly reduces the number of the transistors of the ternary Full Adder cell and do not require any additional power supplies. For instance the conventional CMOS ternary Full Adder cell [20] is composed of more than 200 transistors and needs an additional voltage supply. As an another instance the state-of-the-art CNTFET-based ternary Full Adder cell, which can be considered as two cascaded CNTFET-based ternary Half Adders [6] is composed of 190 CNTFETs and requires an extra voltage supply.…”
Section: The Proposed Ternary Full Adder Cellsmentioning
confidence: 99%
“…However the most efficient radix for implementing switching systems is claimed to be the natural base (e = 2.71823). This infers that the best integral radix is 3 rather than 2 [20] [28]. From the previously proposed works the design of basic ternary logic gates and its application in various circuits can be studied [29]- [32].…”
Section: Introductionmentioning
confidence: 98%
“…From the literature survey, it has been observed that in two-level logic (binary logic), performance degradation occurs due to large area occupied for interconnection purpose [20]. It is broadly studied that in VLSI chip 70% of the area is consumed for interconnection, 20% to insulation and 10% to devices [21].…”
Section: Introductionmentioning
confidence: 99%